Stress dependence of the dislocation core structure and loop nucleation for face-centered-cubic metals. (1st June 2017) - Pi, Z.P.; Fang, Q.H.; Jiang, C.; Liu, B.; Liu, Y.; Wen, P.H.; Liu, Y.W.
Abstract: In face-centered-cubic (fcc) metals, the evolution of Shockley partial dislocations under stress is known to play an important role in plastic deformation. The simulations of the dislocation evolutions, including dislocation dissociation, nucleation and recombination, under applied stress are presented using a phase field dislocation dynamics model that incorporates the γ surface of various fcc metals. As expected, the separation of the leading and trailing partials, termed the equilibrium stacking fault width (SFW), is governed by the details of the γ surface and the external loading conditions. Two important critical stresses, defined as the singular stress and the nucleation stress, are found to determine the stress-dependent evolution mechanism. As a general rule, the SFW increases with the applied stress and diverges when the applied stress exceeds the singular stress. A spontaneous nucleation of partial dislocation loops within the stacking fault (SF) occurs when the applied stress exceeds the nucleation stress. In particular, a new stress-size-dependent nucleation mechanism is observed in the simulations in the case where the singular stress is greater than the nucleation stress for a fcc metal: the nesting loop or nesting dipole can remain in the metastable state without any nucleation even the applied stress is twice as large as the nucleation stress. Graphical abstract: Image 1